Legal Analysis of Illegal Adoption Without Court Determination and Legal Protection of Children's Rights in Indonesia - Arya Wijaya; Wulan Windiarti (Fox Justi : Jurnal Ilmu Hukum, 2026)
The practice of informal or underhand (de facto) child adoption accompanied by the manipulation of population administration documents is widespread within the sociological reality of Indonesian society. This phenomenon triggers juridical issues when bypassing the formal channels of civil court proceedings (voluntair) results in uncertainty regarding the child's civil status, thereby causing vulnerability in substantive civil law protection and the fulfillment of the child's future economic (inheritance) rights. This research carries a fundamental urgency to examine the synchronization of cross-sectoral adoption regulations, test the effectiveness of law enforcement through the lens of legal sociology, and formulate an ideal non-penal (administrative-civil) solution model for child protection. The research method applied is normative juridical, relying on primary, secondary, and tertiary legal materials obtained through library research. The problem-approach is conducted via the statute approach, conceptual approach, and case approach. All legal materials are analyzed qualitatively-normatively using deductive reasoning through the method of legal syllogism as well as legal interpretation methods (rechtsinterpretatie). The theories utilized to dissect the issues in this study are Soerjono Soekanto's Legal Effectiveness Theory and Satjipto Rahardjo's Legal Protection Theory. The research results indicate that the legal regulation of child adoption in Indonesia is pluralistic (encompassing national, customary, and Islamic laws), where the rigid enforcement of penal sanctions in the population sector is deemed ineffective due to the dominance of the community's Legal Culture Factor that prioritizes humanitarian motives, which is harmoniously responded to by the Law Enforcer Factor through humanistic discretionary policies. This policy aligns with the modern sentencing paradigm in the New Criminal Code (Law Number 1 of 2023), which prioritizes restorative justice. In conclusion, the substantive legal protection of de facto foster children must be manifested through administrative-civil legalization channels to ensure that the principle of the best interests of the child is truly realized.